Perilaku Runtuh Balok Beton Bertulang dengan Sengkang Welded Wire Fabric (WWF) - Sudarsana, I Ketut; Deskarta, Putu; Sanjaya, Putu Chandra Wira (Department of Civil Engineering, Diponegoro University, 2019)
The use of Welded Wire fabric (WWF) has been widely tested and proven to behave very well as stirrups in a column, but its behavior has not been widely known when used on beams. This research was conducted to evaluate the behavior of beams with stirrup reinforcement of WWF M4 grid. A total of nine beam specimens with dimensions of 330mm x 180mm x 1500mm were made and tested under monotonic loading until failure loads with three variations of stirrup, where each variation was made of three beam specimens and four concrete cylinders. The concrete was a ready mix concrete with an average compressive strength of 22,875 kN at 28 days. Beams were tested on simply supported with two concentrated loads at a distance of 500 mm from each support. The loads was applied incrementally and the middle span deflections were recorded for each increase in loads. The test results show that the stirrups of WWF M4 grid on beam specimens can increase the shear capacity, stiffness and control the occurrence of the first inclined crack. When compared to conventional stirrups (BJTP ∅ 6mm), beams with WWF M4 stirrups show better behavior.